A family dispute: Rawls versus Habermas - Tomé, Julio (Sofia, 2025)
Rawls affirms the first principle of justice as fairness, stressing that all people should have an equal right to the greatest possible system of equal basic liberties, so that the system of liberties of one person is compatible with those of others. This principle would be chosen within the original position, a situation of impartiality where the parties would not have access to their social, economic and even psychological characteristics. With regard to his P1, Rawls affirms a list of equal basic liberties that would need to be guaranteed in a well-ordered society. And he points out that liberties can be limited when they conflict with other liberties, so they are not seen as absolute. However, the American philosopher affirms that political liberties have a special nature, making the first principle of justice as fairness a principle of equal political participation. Habermas, in turn, criticizes Rawls by stating that political liberties, in Rawls' thought, play merely an instrumental role, as well as the fact that the design of the original position would fail to explain and secure the point of impartial evaluation of deontologically understood principles of justice. In this paper, the central objective will be to investigate whether the criticisms presented by Habermas follow, on which it will be argued that the German philosopher's objections to Rawls, despite having presented important challenges to Rawlsian political liberalism, do not follow.
Keywords: original position; basic fundamental liberties; Rawls; Habermas